2016
DOI: 10.1371/journal.pone.0159080
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNase3 Co-Localizes and Interacts with the Antiviral Defense Protein SGS3 in Plant Cells

Abstract: Sweet potato chlorotic stunt virus (SPCSV; family Closteroviridae) encodes a Class 1 RNase III endoribonuclease (RNase3) that suppresses post-transcriptional RNA interference (RNAi) and eliminates antiviral defense in sweetpotato plants (Ipomoea batatas). For RNAi suppression, RNase3 cleaves double-stranded small interfering RNAs (ds-siRNA) and long dsRNA to fragments that are too short to be utilized in RNAi. However, RNase3 can suppress only RNAi induced by sense RNA. Sense-mediated RNAi involves host suppre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
(91 reference statements)
1
15
0
Order By: Relevance
“…RNase III of SPCSV increases the accumulation of SPFMV by suppressing the plants’ RNAi defence system of plants [8, 48]. However, in our study, RNase III transgenic plants infected with SPFMV (R3-F) showed more severe disease symptoms than did those co-infected with SPCSV and SPFMV (Wt-FC) in many aspects of growth (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…RNase III of SPCSV increases the accumulation of SPFMV by suppressing the plants’ RNAi defence system of plants [8, 48]. However, in our study, RNase III transgenic plants infected with SPFMV (R3-F) showed more severe disease symptoms than did those co-infected with SPCSV and SPFMV (Wt-FC) in many aspects of growth (Fig.…”
Section: Discussionmentioning
confidence: 66%
“…Several viral proteins, e.g., PlAMV TGB1, TYLCV V2, SPCSV RNase 3, and RSV P2, have been found to target SGS3 to enhance host susceptibility (21)(22)(23)(24). These VSRs have evolved distinct mechanisms to inhibit SGS3 functions.…”
Section: Discussionmentioning
confidence: 99%
“…Many VSRs suppress RNA silencing via sequestration of virus-derived siRNAs and inactivation of AGO proteins (mainly AGO1) (18)(19)(20). In contrast, some other VSRs, such as V2 of Tomato yellow leaf curl virus (TYLCV), P2 of Rice stripe virus (RSV), TGB1 of Plantago asiatica mosaic virus (PlAMV), and the class 1 RNase III endoribonuclease (RNase 3) of Sweet potato chlorotic stunt virus (SPCSV), target other RNA silencing components, e.g., SGS3, to attenuate plant antivirus immunity (21)(22)(23)(24).…”
mentioning
confidence: 99%
“…As the partner of RDR6, SGS3 can stabilize the 5’ overhang of dsRNAs, prevent their degradation, and recruit them for facilitating RDR6-mediated dsRNA synthesis [ 7 , 8 , 9 , 10 ]. Recent reports have shown that that SGS3 could be targeted by several VSRs or endogenous RNA silencing suppressor [ 11 , 37 , 38 , 39 , 40 , 41 , 42 ]. We showed NbSGS3 is an essential component of PTGS and is closely associated with geminivirus resistance in N. benthamiana .…”
Section: Discussionmentioning
confidence: 99%